Factores que influyen en la prevalencia de la neumonía en pacientes que acuden al Hospital de Especialidades Fuerzas Armadas N°1, en el periodo octubre 2019 – marzo 2020 - Paredes Chonillo, Evelin Estefanía (2020)
Pneumonia is an acute respiratory infection that affects the lung parenchyma; it can be caused by different microorganisms and is the leading individual cause of infant death worldwide. It comprises one of the top 10 causes of morbidity and mortality in Ecuador, with Pichincha being the province with the highest prevalence during the last two years. There are many factors that influence the prevalence of pneumonia in patients who go to the Specialities Armed Forces Hospital No. 1, which is why its study is necessary since, by virtue of statistics, pneumonia is a public health problem. There are many factors that predispose the individual; some of them are modifiable, as in the case of smoking. The methodology applied in this research - deductive qualitative-quantitative methodology - applied depending on the place, is based in books and also on the field. According to the level of study, it is descriptive, observational, from the field and bibliographic, and of cross-dimension. For the collection of data, the observation and analysis of medical records of 33 patients admitted with a diagnosis of pneumonia in the pulmonology service of the Specialities Armed Forces Hospital No. 1 was processed during the period October 2019 - March 2020. The graphs show the percentage of the population most affected by age groups, sex, and pathologies among others. Considering the modifiable habits, educational talks are proposed for patients and families. This initiative aims to raise awareness among people to reduce the number of cases of pneumonia in this care home.